Edukasi Tentang Pengetahuan Anemia Pada Remaja di SMA Negeri III Aceh Tenggara - Lestari, Siti; Lestari, Fika; Bahri, Serli; Br Karo, Dina Andriani (Universitas Negeri Gorontalo, 2026)
Anemia is a micronutrient problem found in Indonesia and even globally. Anemia is a condition in which the number of red blood cells or hemoglobin concentration in the blood is below normal. Hemoglobin is needed to carry oxygen throughout the body. Adolescents without anemia are 37 times more likely to achieve academic success than those with anemia.